EVALUATION OF DOMESTIC WASTEWATER TREATMENT WITH COMMUNAL WASTEWATER TREATMENT (IPAL) IN SIABU VILLAGE, SALO DISTRICT, KAMPAR DISTRICT - Melia Lusiana; Syafruddin Nasution; Sofia Anita (Fakultas Perikanan dan Kelautan, Universitas Riau, 2020)
The communal domestic wastewater treatment plant functions to collect and treat domestic wastewater at the source location according to the communal scale treatment capacity. The communal Wastewater Treatment Plant (IPAL) in Suka Damai Hamlet, Siabu Village was built since 2017 using the Anaerobic Baffled Reactor (ABR) system. This study aims to evaluate the Communal IPAL by analyzing the quality of wastewater compared to PerMenLH No. 68 of 2016, calculating the effectiveness of WWTP, and analyzing community participation in IPAL management. To compare thequality of wastewater before and after treatment using the Paired t-test method with a significance level of 0.05%, Direct sampling of wastewater on-site in the morning and evening, each with three replications and then analized at the Riau University Fisheries Laboratory.The results showed that the quality of wastewater exceeds the quality standard for the Total Coliform parameter, while the pH, BOD, COD and TSS parameters do not exceed the environmental quality standard. The Communal IPAL at RT 01 RW 02 Dusun Suka Damai, Siabu Village has not been efficient in treating domestic wastewater and the role of the community is still at the level of manipulation. Communal WWTP management needs to be improved so that the effluent quality and processing efficiency values meet the predetermined regulatory standards.